PERANAN ETNIS ARAB MELAYU DALAM PENGEMBANGAN ISLAM DI KOTA JAMBI AWAL ABAD XX - Lilis Sucialinda (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2019)
AbstractThis study to determine the origin of Malay Arab ethnicity and its role in the development of Islam in Jambi City in the early XX century. The study uses historical methods which have several stages, namely heuristics, criticism, interpretation, and historiography. The results of the study provide information that most of the ethnic Arabs who settled in the city of Jambi originated from the Hadramaut region in the Southern Arab States, while the role of Malay ethnic groups in the development of Islam in the city of Jambi was quite large starting from the entry of Islam in Jambi brought by Akhmad Salim in the century XV continued by Tuanku Keramat Tambak (Sayyid Husein Baragbah) and continued by Muhammad Syufi Bafadhal. The efforts of ethnic Arabs in the development of Islam in the city of Jambi in the early XX century were carried out by the most respected figures, Sayyid Idrus Hasan Al Jufri (Prince Wiro Kesumo) and Prof. Sheikh HMO Bafadhal, who carried out construction of places of worship (mosques), school construction (schools) Madrasa), proselytizing as well as being scholars.Keywords: Ethnic Arabic, Role, Jambi City. AbstrakPenelitian ini bertujuan untuk mengetahui asal usul etnis arab melayu serta perannya dalam pengembangan Islam di Kota Jambi pada awal abad XX. Penelitian menggunakan metode sejarah yang memiliki beberapa tahapan yaitu heuristik, kritik, interpretasi, dan historiografi. Hasil penelitian memberikan keterangan bahwa sebagian besar etnis Arab yang menetap di Kota Jambi berasal dari daerah Hadramaut di Negara Arab bagian Selatan, Sementara peran etnis Arab melayu dalam pengembangan Islam di Kota Jambi cukup besar dimulai dari masuknya Islam di Jambi yang dibawa oleh Akhmad Salim pada abad XV dilanjutkan oleh Tuanku Keramat Tambak (Sayyid Husein Baragbah) dan dilanjutkan Muhammad Syufi Bafadhal. Usaha-usaha etnis Arab dalam pengembangan Islam di Kota Jambi di awal abad XX dilakukan oleh tokoh yang paling terpandang yaitu Sayyid Idrus Hasan Al Jufri (Pangeran Wiro Kesumo) dan Prof Syekh HMO Bafadhal, mereka melakukan Pembangunan tempat peribadatan (Masjid), pembangunan sekolah (Madrasah), da’wah serta sampai menjadi para ulama.Kata Kunci : Etnis Arab, Peran, Kota Jambi.